Rancang Bangun Alat Surgical Smoke Evakuator dengan Hepa Filter sebagai Penyaring Udara - Muhammad Adham Fathurozi Ramadhan; Andi Kurniawan Nugroho; Patrisius Kusi Olla (Asosiasi Dosen Muda Indonesia, 2025)
The smoke generated from surgery contains harmful particles, including carcinogenic substances and microorganisms, which can endanger the health of medical personnel and patients. To reduce this risk, the design and testing of a Surgical Smoke Evacuator tool equipped with a HEPA filter as an air filter media is carried out. This tool utilises an Arduino Uno microcontroller as the main controller, an MQ-2 sensor to detect smoke, a DC motor as a suction system, and an I2C LCD to display information. The tool is also equipped with a button to adjust the motor speed level manually. Testing is done by evaluating the voltage and RPM of the motor in various conditions.